MAXMUD QAShQARIYDIŃ «DEVONU LUǴATIT TÚRK» MIYNETINDEGI «JÚREK» KONCEPTINIŃ BERILIWI - Qayıpnazarova, U.U. (ILIM hám JÁMIYET, 2025)
The article is devoted to the study of Mahmud Kashgari's "Devoni lug'at it turk" in Karakalpak linguistics and the study of somatic phraseological units in it. Also, somatic phraseological units with the concept of "heart" in the line of proverbs and sayings in the work "Devoni-lug'at it turk" were analyzed from a linguocultural point of view.